Comparison of Thessaly Test with Joint Line Tenderness and McMurray Test in the Diagnosis of Meniscal Tears - B, Shekarchi; A, Panahi; SA, Raeissadat; N, Maleki; S, Nayebabbas; P, Farhadi (Malaysian orthopaedic journal, 2020)
Meniscus injuries are the most frequent problem of the knee. The aim of this study was to investigate the accuracy of the Thessaly test and comparing it with those of McMurray and Joint-line tenderness tests for diagnosing meniscal tears. This study was designed as a prospective observational one done in an outpatient clinic at a university hospital. 106 patients with knee pain and 82 age-matched control were included during study period (from February 2014 to January 2015). Each patient was clinically examined with McMurray, Thessaly, and joint line tenderness tests. Then, the findings were matched by MRI and arthroscopic findings. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy were calculated as main outcomes. Based on MRI, Thessaly was the most sensitive for medial meniscus tears (56.2%), while McMurray and joint-line tenderness were more specific (89.1% and 88.0%, respectively). For lateral meniscus tears, McMurray was the most sensitive (56.2%) and all were specific (McMurray 89.6%, Thessaly 88.4%, joint-line tenderness 90.2%). With arthroscopy, Thessaly was the most sensitive for medial meniscus (76.6%), while McMurray and joint-line tenderness were more specific (81.0%, and 81.0%). Agreement with arthroscopy was the highest with McMurray (for medial meniscus kappa=0.40, p<0.001, and for lateral meniscus kappa=0.38, p=0.002). The Thessaly can be used to screen for medial meniscus tears. McMurray and joint-line tenderness should be used for suspected medial meniscus tears. For lateral meniscus, McMurray is appropriate for screening and all the tests are useful in clinic.